Clinicopathological features and immunohistochemical detection of antigens in acute experimental Streptococcus agalactiae infection in red tilapia (Oreochromis spp.) - Abdullah, Syuhaidah; Omar, Noraini; Mohd Yusoff, Sabri; Emikpe, Benjamin Obukowho; Tanko, Polycarp Nwunuji; Hanan, Latifah; Samad, Jamil (SpringerOpen, 2013)
This study investigates the clinicopathological features of acute experimental streptococcosis in red tilapia using various routes of infection; intraperitoneal (IP), immersion (IM) and immersion cut (IC). Twenty four red tilapia in duplicates were inoculated intraperitoneally with 109 CFU/ml of S. agalactiae while another sets: intact, one with sharp cut at the tail end were exposed to bacterial inoculums 109 CFU/ml diluted in water while two groups of control fish were similarly manipulated. Clinical signs were recorded; samples from the gills, brain, eyes and kidneys were also taken for bacterial isolation and histopathology. Immunohistochemistry (IHC) and polymerase chain reaction (PCR) were employed to detect the antigen. The diseased fish showed skin, fin haemorrhages and exophthalmia with obvious signs in IP at 2 hpc followed by IC and IM at 4 hpc. The lesions were noticed earlier in the kidney and most severe in IP. IHC detected antigen as early as PCR and isolation with intense staining in blood vessel lumen and wall, macrophages in choroid, focal haemorrhage in the renal interstitium and meninges especially in IP followed by IC and IM. The immunolocalisation of the antigen described for the first time further explain the pathogenesis of streptococcosis in red tilapia.